2004
DOI: 10.1111/j.1601-5223.1993.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Synaptonemal Complexes from the Grasshopper Chorthippus Jacobsi: Pachytene and Zygotene Observations

Abstract: Pachytene and zygotene stages have been analysed on silver stained spreads of synaptonemal complexes (SCs) from Chorthippus jacobsi spermatocytes. SC lengths are compared to those obtained from C‐banded mitotic metaphases. The pattern of meiotic pairing initiation and progression is described. In the submetacentric bivalents it is initiated from both chromosomal ends whereas in acrocentric bivalents two potential pairing initiation points are located in the long arms, the short arms remaining as late pairing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…2 J). It is interesting to point out that the sequence of appearance, development and pairing of the SMC3 axes is in close agreement with that displayed by AE/LEs and SC under electron microscopy [Santos et al, 1993]. As previously mentioned, ␥ -H2AX is restricted to unpaired portions of SMC3 axes during zygotene ( fig.…”
Section: The Standard Scenario: the Onset Of Recombination Precedes Ssupporting
confidence: 62%
“…2 J). It is interesting to point out that the sequence of appearance, development and pairing of the SMC3 axes is in close agreement with that displayed by AE/LEs and SC under electron microscopy [Santos et al, 1993]. As previously mentioned, ␥ -H2AX is restricted to unpaired portions of SMC3 axes during zygotene ( fig.…”
Section: The Standard Scenario: the Onset Of Recombination Precedes Ssupporting
confidence: 62%
“…The occurrence of interstitially located telomeric sequences on macrochromosomes is connected with an increase in the number of sites where formation of SCs is initiated, which explains why synapsis is achieved more rapidly. SANTOS et al (1993) observed that in submetacentric bivalents SC formation begins from subtelomeric regions of chromosomes. Two potential sites of initiation exist in acrocentric bivalents, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In geese the largest macrochromosomes are submetacentric, whereas microchromosomes are acrocentric, so the theory of SANTOS et al (1993) and the presence of interstitial telomeric sequences in chromosomes may provide an explanation to why macrochromosomes and not microchromosomes undergo synapsis first. Moreover, compared with macrochromosomes, microchromosomes are characterised by a lower adeninethymine content, accompanied by a higher guanine-cytosine content (FILLON et al 1998;GREGORY 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of interstitially located telomeric sequences on macrochromosomes is connected with an increase in the number of places where the formation of SCs is initiated, which explains why synapsis is achieved quicker. Santos et al (1993) observed that in submetacentric bivalents synaptonemal complex formation begins from subtelomeric regions of chromosomes. In acrocentric bivalents there exist two potential initiation sites which are in the distal and proximal parts of the q arm.…”
Section: Heterochromosomal Synapsismentioning
confidence: 99%
“…9. Chromatin organisation in one-day-old gosling cells; isolation - Counce & Meyer (1973), staining -Howell & Black (1980 In geese the largest macrochromosomes are submetacentric whereas the largest microchromosomes are acrocentric, so the theory of Santos et al (1993) and the presence of interstitial telomeric sequences in chromosomes may explain why it is macrochromosomes and not microchromosomes that are the first to undergo synapsis. Moreover, compared with macrochromosomes, microchromosomes are characterised by a lower adenine-thymine content which is accompanied by a higher guanine-cytosine content (Fillon et al, 1998;Gregory, 2002).…”
Section: Heterochromosomal Synapsismentioning
confidence: 99%